Novel NTRK1 mutations in Chinese patients with congenital insensitivity to pain with anhidrosis - Geng, Xingzhu (Mol Pain, 2018)
Congenital insensitivity to pain with anhidrosis (CIPA) is a rare autosomal recessive disorder, characterized by loss of algesthesis and inability to sweat. CIPA is known to be caused by mutations in the neurotrophic tyrosine kinase receptor type 1 gene (NTRK1). However, the details of NTRK1 mutations in Chinese CIPA patients remain unclear. In the present study, we recruited 36 CIPA patients from 34 unrelated families in mainland China. Blood samples from these patients and their available familial members were collected and subjected to genetic analysis. We identified 27 mutations in NTRK1 from this cohort, including 15 novel mutations. Interestingly, we discovered two forms of novel recurrent mutations: the first was a large intragenic deletion c.429–374_717 + 485del mediated by recombination between Alu elements, and the second was a deep intronic substitutions c.[851–798C > T;851–794C > G]. All probands were homozygotes or compound heterozygotes of these mutations. Current findings expand our knowledge about the mutation spectrum of NTRK1 in Chinese CIPA patients and provide more evidence for precise diagnosis of the clinically suspected patients with CIPA.